Learning Motivation and Parenting Patterns: Factors that Influence Elementary School Students' Science Learning Outcomes - Agustina, Santi; Margunayasa, I Gede (Journal for Lesson and Learning Studies, 2024)
Students have low learning motivation, which impacts low learning outcomes. In addition, parenting style also affects student learning outcomes. This research aims to analyze parents' learning motivation and parenting style about the science learning outcomes of elementary school students. This research is exposed to facto research on learning motivation and parenting patterns on student learning outcomes. The population in this study amounted to 141 students. This study uses a saturated or census sampling technique. The methods used in collecting data are observation and questionnaires. The instrument used to collect data is a questionnaire sheet. The data analysis technique used in this study is inferential statistical analysis. The research results are the first hypothesis obtained that there is a positive and significant relationship between learning motivation and science learning outcomes of fifth-grade students. The second hypothesis found a positive and significant relationship between parenting parents and the science learning outcomes of fifth-grade students. The third hypothesis found a positive and significant relationship between learning motivation and parenting styles with students' science learning outcomes. It was concluded that parents' learning motivation and parenting style could improve the science learning outcomes of fifth-grade students.